ASPECTS OF THE HARMONY OF CULTIC CHOIRS FROM OEDIPUS BY GEORGE ENESCU - Constanţa CRISTESCU (Studia Universitatis Babeş-Bolyai. Musica, 2011)
It approaches to analysis some choral moments of cultic ritual of George Enescu's opera Oedipus, in the light source of inspiration to those of ancient Greek and Byzantine succession. The concept of harmony it is used in both meanings, given in Greek antiquity and in contemporary Enescu's. The case study is conducted on the four moments of the old Athenian cultic invocation of Act IV. It shows that the modal structures that Enescu uses are found in the diatonic and chromatic harmony of the ancient modal system, having continuity in the modal systems of Byzantine succession, until today. Also it is demonstrated the use by George Enescu of the ancient system of modulation (metabolos), used in the harmonic plane, integral, horizontal and vertical through innovative solutions.